2002
DOI: 10.1002/hbm.10026.abs
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous measurements of cerebral oxygenation changes during brain activation by near-infrared spectroscopy and functional magnetic resonance imaging in healthy young and elderly subjects

Abstract: Near infrared spectroscopy (NIRS) and functional magnetic resonance imaging (fMRI) both allow non-invasive monitoring of cerebral cortical oxygenation responses to various stimuli. To compare these methods in elderly subjects and to determine the effect of age on cortical oxygenation responses, we determined motor-task-related changes in deoxyhemoglobin concentration ([HHb]) over the left motor cortex in six healthy young subjects (age 35 +/- 9 years, mean +/- SD) and five healthy elderly subjects (age 73 +/- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 29 publications
5
40
1
Order By: Relevance
“…Our data agree well with Ogawa et al (1993) and Buxton et al (1998), which assume that the BOLD signal arises mainly from magnetic disturbances caused by the paramagnetic deoxy-Hb. Our data are also consistent with simultaneous fMRI and fNIRS experiments showing a high correlation between the BOLD signal and deoxy-Hb (Kida et al, 1996;Mehagnoul-Schipper et al, 2002;Punwani et al, 1997Punwani et al, , 1998Toronov et al, 2003) and with Pouratian et al (2002) who showed a high temporal and spatial correlation between the BOLD signal and optical intrinsic signals measured at 610 nm (particularly sensitive to deoxy-Hb) in humans. Differences to Strangman et al (2002), who found a lower correlation of the BOLD signal with deoxy-compared with oxy-Hb during finger flexion/ extension motor activation, may be explained by their less (three) subjects, different (block) design, their shorter emitter -detector separation (Germon et al, 1999), and non-linear changes of oxyHb in relation to deoxy-Hb in the motor cortex (Wolf et al, 2002).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our data agree well with Ogawa et al (1993) and Buxton et al (1998), which assume that the BOLD signal arises mainly from magnetic disturbances caused by the paramagnetic deoxy-Hb. Our data are also consistent with simultaneous fMRI and fNIRS experiments showing a high correlation between the BOLD signal and deoxy-Hb (Kida et al, 1996;Mehagnoul-Schipper et al, 2002;Punwani et al, 1997Punwani et al, , 1998Toronov et al, 2003) and with Pouratian et al (2002) who showed a high temporal and spatial correlation between the BOLD signal and optical intrinsic signals measured at 610 nm (particularly sensitive to deoxy-Hb) in humans. Differences to Strangman et al (2002), who found a lower correlation of the BOLD signal with deoxy-compared with oxy-Hb during finger flexion/ extension motor activation, may be explained by their less (three) subjects, different (block) design, their shorter emitter -detector separation (Germon et al, 1999), and non-linear changes of oxyHb in relation to deoxy-Hb in the motor cortex (Wolf et al, 2002).…”
Section: Discussionsupporting
confidence: 91%
“…Several recent studies compared the hemodynamic response to brain activation as measured by functional near-infrared spectroscopy (fNIRS) with another imaging method, such as functional magnetic resonance imaging (fMRI) (Hoge et al, 2005;Kennan et al, 2002;Kleinschmidt et al, 1996;Mehagnoul-Schipper et al, 2002;Obrig et al, 2000b;Seiyama et al, 2004;Siegel et al, 2003;Strangman et al, 2002;Toronov et al, 2001aToronov et al, ,b, 2003Wenzel et al, 2000) or positron emission tomography (PET) . While optical measurements are poorer in spatial resolution and depth penetration than fMRI, they are biochemical specific and, consequently, provide information about changes in oxy-, deoxy-, and total hemoglobin (Hb) with a high temporal resolution (Hoshi, 2003;Villringer and Chance, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…When we use activation and deactivation in the present article, therefore, we are using the operational definition, unless a more general meaning is explicitly stated. The decrease in [deoxy-Hb] corresponds to an increase in BOLD contrast, as has been shown by several studies (Kleinschmidt et al, 1996;Mehagnoul-Schipper et al, 2002). If no change in [deoxyHb] is seen (and the concomitant increase in [oxy-Hb] is therefore judged the relevant change, indicating cerebral activation [using the general sense of the word]) the interpretation of the results should at least consider that the alleged activation would not show in a BOLD-contrast fMRI study!…”
Section: Physiology Of the Signalmentioning
confidence: 78%
“…Studies of functional brain activity acquired simultaneously by fMRI and near-infrared techniques have increased significantly in recent years (Boas et al, 2004a,b;Hoge et al, 2005;Horovitz and Gore, 2004;Kennan et al, 2002;Mehagnoul-Schipper et al, 2002;Okamoto et al, 2004;Seiyama et al, 2003Seiyama et al, , 2004Strangman et al, 2002;Toronov et al, 2001a,b). In order to be able to compare the results of both techniques, it is helpful to apply the same analysis techniques to the data from both modalities.…”
Section: Discussionmentioning
confidence: 99%